Konsep Diri dan Resiliensi Orangtua yang Memiliki Anak Tunagrahita - Eugennia Sakanti Putri; Ketut Suryani; Novita Elisabeth Daeli (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
Mentally retarded is a child who has intelligence below average. Mentally retarded children have an inability to take care of themselves, help themselves, communicate, adapt to the environment and simple skills. Mentally retarded itself has a high level of dependence on other people. Parents are one of the roles that are needed by children with intellectual disabilities in achieving their growth and development. Where the general reaction of parents when they find out that their child has special needs includes shock, shame and depression, and parents in having children with special needs usually try to reject the reality. For this reason, self-concept and parental resilience are very important in providing guidance and assistance to the child until he grows up. This study aims to see an overview of self-concept and resilience of parents who have children with mental retardation special needs. This type of research uses quantitative descriptive methods, the population in this study are all parents who have children aged 5-17 years, totaling 41 respondents and the number of samples in the study is 41 respondents with sample skills using total sampling and univariate analysis. The majority of self-concepts of parents who have children with mental retardation in the positive category are 24 respondents (63.2%). The majority of the resilience of parents who have children with mental retardation in the high category are 22 respondents (57.9%). So parents who have children with special mental retardation needs in this study have a positive self-concept and high resilience. Keywords: Self-concept, resilience, parent, mentally disabled